Sense of Coherence as a Predictor of Positive Psychological Outcomes Among Adults - Sajid Mahmood Alvi; Andleeb Akhtar; Noman Aftab (Journal of Management Practices, Humanities and Social Sciences, 2021)
The purpose of the current study was to seek out the Sense of Coherence (SOC) as a predictor of well-being, happiness, life satisfaction, and tension. Standard self-report questionnaires were used to collect data. Sample of the present study comprised (N = 200). Psychometric properties of variables, reliability analysis, Pearson correlation, and linear regression analysis were applied to analyze the data. The hypotheses are fully accepted. SOC positively predicts well-being, happiness, and life satisfaction, while a SOC negatively predicts stress. A purposive sampling technique was used, thus the study was quantitative. The current investigation is an important expansion in writing on the hypothesis of the feeling of intelligibility. The present study contributes to the theory by suggesting the path to well-being, stress, happiness, and life satisfaction. The present study identified that the SOC positively predicts well-being, happiness, and life satisfaction. The research findings are helpful for the well-being, happiness, and life satisfaction of life for the betterment of a SOC. Prior research was conducted on the SOC and mental health outcome in subcultures of Pakistan', but this study used a sample of different peoples to cope with their difficulties. Past researches were based on cross-cultural, and now present research findings also confirmed the theories in a collectivistic culture. This study predisposes Pakistani research to work on the salutogenic model and explore the new perspective of SOC in Asian culture.